Empowering the Ummah: Innovative Economic Strategies for Development - Rizapoor, Habiburrahman (SocioHumania: Journal of Social Humanities Studies, 2024)
This paper mainly discusses the strategies for the economic development of the Islamic countries, to understand better what economic development is, it is necessary to understand the definition of some terms such as economy, strategy, economic strategy, and Islamic economy. After the definition of the terms, the paper discusses some characteristics of a strategy that can work for of a country or an organization, objectives of economic strategy, and characteristics of economic strategy which says that a strategy should be inclusive, directed to an open system, should be mandatory time based, should be clear and persuasive, make sure the participation for all, should pass the stages of making strategy, have to be flexible and should allocate resources. After that, the topic discusses 6 kinds of economic strategies that countries use for their economic development such as monetary strategy, open economy strategy, manufacturing strategy, the green revolution strategy, redistribution strategy, and socialist development strategy. Then the paper discusses an understanding of welfare and it generally includes the basic needs of a human, and then the paper mentions some points about the economic welfare according to Islam, that Islam encourages us to work and have the commitment for developing the world as we are also ordered to worship Allah and make our life better in the hereafter life, and finally I finished the discussion by a conclusion from the paper.